2007
DOI: 10.1542/peds.2007-0440
|View full text |Cite
|
Sign up to set email alerts
|

Motor and Executive Function at 6 Years of Age After Extremely Preterm Birth

Abstract: BACKGROUND. Studies of very preterm infants have demonstrated impairments in multiple neurocognitive domains. We hypothesized that neuromotor and executive-function deficits may independently contribute to school failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
237
3
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 373 publications
(275 citation statements)
references
References 32 publications
25
237
3
10
Order By: Relevance
“…A number of studies have documented that many prematurely born children eventually experience visuoperceptive deficits such as problems with form orientation, visuo-motor integration, visual motion processing and attention (Jakobson et al 2006;Marlow et al 2007). The present study confirms this correlation between visual acuity on one hand and performance score (but not the verbal score) of the WPPSI-R test and fine and gross motor function of the ABC movement tests on the other.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have documented that many prematurely born children eventually experience visuoperceptive deficits such as problems with form orientation, visuo-motor integration, visual motion processing and attention (Jakobson et al 2006;Marlow et al 2007). The present study confirms this correlation between visual acuity on one hand and performance score (but not the verbal score) of the WPPSI-R test and fine and gross motor function of the ABC movement tests on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely preterm children are at heightened risk of deficits in IQ, [1][2][3][4][5][6] attention, 7,8 executive function, 4,6,[9][10][11][12][13][14] processing speed, [15][16][17] visual perception, 6,14 and visual-motor function. 6,14 Neurocognitive deficits are accompanied by delays in academic attainment.…”
mentioning
confidence: 99%
“…6,14 Neurocognitive deficits are accompanied by delays in academic attainment. 6,[18][19][20] These deficits vary in their severity according to the degree of prematurity, whether measured by birth weight 6 or gestational age (GA).…”
mentioning
confidence: 99%
“…Studies have suggested that early self-control abilities (e.g. inhibitory or effortful control) may mediate effects of preterm birth on cognitive outcomes [7,8] and later achievement [9,10]. Inhibitory control predicts the development of the executive attention network [11] and is related to children's executive functions (EFs), high-level cognitive abilities that allow humans to show adaptive, goal-directed behavior in complex situations [12].…”
mentioning
confidence: 99%